Unravelling Cocoa Drying Technology: A Comprehensive Review of the Influence on Flavor Formation and Quality - Margareth Santander; Vanessa Chica; Hugo A. Martínez Correa; Jader Rodríguez; Edwin Villagran; Fabrice Vaillant; Sebastián Escobar (Foods)
Cocoa quality serves as a differentiating factor that provides monetary and non-monetary benefits to farmers, defined by the genotype, agroecological conditions of cultivation, and the post-harvest processes involved in transforming seeds into cocoa beans, including harvesting, pre-conditioning, fermentation, and drying. Drying plays a crucial role in ensuring the sensory, chemical, and microbiological quality of the beans, as simultaneous mass and heat transfer phenomena occur during this process, along with chemical reactions (both enzymatic and non-enzymatic) that influence the concentration and dynamics of phenolic compounds, organic acids, methylxanthines, and the formation of volatiles, directly impacting flavor development in cocoa beans. This paper comprehensively reviews cocoa drying methods, variables, and equipment and analyzes their impact on these flavor-determining compounds. The findings highlight that drying significantly contributes to the production of differentiated and specialty quality traits. An integral relationship between the methods, operating variables, and drying equipment applied to cocoa and their implications for the volatile and non-volatile compounds is described.